2020
DOI: 10.3389/fpsyg.2020.572980
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction Benefits Psychological Well-Being, Sleep Quality, and Athletic Performance in Female Collegiate Rowers

Abstract: Factors such as psychological well-being, sleep quality, and athletic coping skills can influence athletic performance. Mindfulness-based interventions, including mindfulnessbased stress reduction (MBSR), have been shown to benefit these factors, suggesting they may, at least indirectly, benefit athletic performance. Moreover, while mindfulness training has been linked to better accuracy in some high-precision sports, whether it can improve non-precision elements of athletic performance is unclear. The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
58
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 49 publications
8
58
0
4
Order By: Relevance
“…Mindfulness and psychological skills-based techniques have been used as means to promote athletes' mental toughness and improved performance outcomes [94,[97][98][99]. Training in mindfulness has been shown to improve stress coping among female athletes [100].…”
Section: Trainings and Interventions That Foster Mental Skills For Psychological Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness and psychological skills-based techniques have been used as means to promote athletes' mental toughness and improved performance outcomes [94,[97][98][99]. Training in mindfulness has been shown to improve stress coping among female athletes [100].…”
Section: Trainings and Interventions That Foster Mental Skills For Psychological Resiliencementioning
confidence: 99%
“…Mental skills training educates athletes on how to improve strategies such as imagery, self-talk, goal setting, and arousal regulation [93,102]. While these interventions may vary somewhat in terms of approach, there is evidence that both tactics positively impact athlete performance [94,[97][98][99]. In addition, the consistent provision of motivational feedback is important to encourage and inform athletes about what has been and is effective in developing resilience [21].…”
Section: Trainings and Interventions That Foster Mental Skills For Psychological Resiliencementioning
confidence: 99%
“…Except for another cross-sectional study that observed the relationship between mindfulness and psychological skill, this study has also examined the alterations of mindfulness and psychological skills following a mindfulness-based intervention [ 9 , 42 , 43 , 44 ]. Vidic, St. Martin, and Oxhandler [ 42 ] found that ACSI-28 overall scores were significantly increased among NCAA women basketball athletes following a 10-session mindfulness training, and a similarly significant improvement was observed in concentration, self-confidence/achievement motivation, goal setting/mental preparation, coping with adversity, peaking under pressure, and a decrease in perceived stress following mindfulness training.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the qualitative results also found that mindfulness training increases awareness of the ability of mindfulness. Jones, Kaur, Miller, and Spencer [ 43 ] also adopted ACSI-28 to explore the effects of the eight-week mindfulness training for rowers, and they observed that the rowers improved their mindfulness level, exercise coping ability, and athletic performance. Similar results were achieved for handball athletes, who after an eight-week mindfulness intervention improved their coping with adversity, coachability, concentration, goal-setting, mental preparation, and freedom from worry [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mental ability is one of primary foundations for successful sport performance (Kim et al, 2015), and mindfulness has recently been recognized as a novel aspect of sport-related mental ability (Jones et al, 2020). Mindfulness is believed to reflect both focus on and awareness of one's moment-to-moment experiences through a non-judgmental attitude (Kabat-Zinn, 2003;Creswell, 2017).…”
Section: Introductionmentioning
confidence: 99%